Network Security Risk Assessment Index System and Calculation for Virtual Power Plant - Ke YANG; Dong WANG; Da LI; Wangjun ZHANG; Ga XIANG; Jun LI (Zhongguo dianli)
In this paper, we propose a multidimensional dynamic risk assessment index system for the new system of virtual power plants. Firstly, based on the characteristics of the virtual power plant, a static risk assessment index system is built; a dynamic risk assessment index system is constructed, based on the evolution mechanism of attack paths, and collects data from information, physical and the information physical sides. Then, we propose a quantitative assessment method. Finally, the simulation experiment is carried out to validate the multi-dimensional dynamic risk assessment index system proposed in this paper, which can assess the network risk of the virtual power plant, identify potential risks, and propose valid enhancement measures.